THE ISSUES OF MICROCLONAL PROPOGATION AND THE WAYS OF THEIR OVER OVERCOME (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The information on microclonal propogation of two species of Ferula L.: Ferulatadshikorum Pimenov and Ferula sumbul (Kauffm.) Hook.f. (Apiaceae Lindl.), and two speciesof Ungernia Bunge: Ungernia sewertzowii (Regel) В.Fedtsch. and Ungernia victoris Vved. ExArtjush (Amaryllidaceae J.St.-Hil.), and about the issues which arise in microclonal propogation,and particularly in microclonal propogation of these four valuabla medicinal plant species.
Keywords: microclonal propogation, medical plants, conservation.